The Dolphin - Coombs, Roy; Nang ChanYeema (New York, USA Watermill Press, 1983)
Decribes the natural environment, physical characteristics, and behavior of the dolphin, a mammal with fins that lives in family groups in the temperate waters of the sea.
Keywords: Juvenile Nonfiction